Save Talent of Banking Sector of Pakistan: Mediating Job Satisfaction between Job Stress and Employee Turnover Intention - Munwar Hussain Pahi (International Review of Management and Marketing, 2016)
Job stress is a noteworthy issue in the banking sector of Pakistan and it is issue for both employer and employees. Main purpose of the study mediating job satisfaction between job stress and employee turnover intention. Convenience sampling used for data collection from banking employees and received the 254 questionnaires for data analysis and using the SmartPLS 0.2. Findings of the study job stress and turnover intention has positive relationship further job satisfaction mediating between the job stress and turnover intention. Implication and limitation discussed.